Investigating the Concept of Absurdity in A Doll’s House by Henrik Ibsen: A Critical Study - Pour, Fatemeh Karim; Abshavi, Modgan (International Journal of Linguistics, Literature and Translation, 2021)
This study aimed at investigating the concept of absurdity in A Doll’s House by Henrik Ibsen. Henrik Ibsen’s play A Doll’s House is the primary source in the present study. The data that is applied in this paper belongs to library studies and research since the focus is on or literary works and materials. The results showed that miscommunication is one of the themes of absurdity, which was identified in the present play. There is a master-slave relationship, one of the themes of absurdism, between Nora and Helmer, which can be traced in the play. Materialism is also portrayed in the play as one of the themes of absurdism. The relationships between characters are based on profit. Telling lies, which can be a sign of absurdism, is shown in the play.